Fiscal Policy's Role in Economic Resilience to Climate Shocks - Armon Rezai; Franz Ruch; Rishabh Choudhary; John Nana Darko Francois (CESifo GmbH, 2024)
The impacts of climate change on developing economies are becoming increasingly severe, creating challenges for risk management and requiring enhanced levels of resilience. This paper explores how to mitigate the effects of such climate shocks on developing economies, placing a particular focus on the role fiscal policy in creating and strengthening an economy's resilience. Using data on natural disasters, the analysis shows that economies with constrained fiscal space experience more pronounced negative effects. In an application to a small open economy, the paper tests the presence of the non-linearity of short- and long-run disaster impacts in the World Bank's macroeconomic and fiscal model and illustrates the importance of fiscal policy in mitigating shocks.
Keywords: H20; H12; O44; O47; Q54; 330; fiscal policy; economic resilience; climate; natural disasters